2014
DOI: 10.1063/1.4894502
|View full text |Cite
|
Sign up to set email alerts
|

Molecular simulation study of role of polymer–particle interactions in the strain-dependent viscoelasticity of elastomers (Payne effect)

Abstract: The strain-amplitude dependence of viscoelastic behavior of model crosslinked elastomers containing various concentrations of spherical nanoparticles (NPs) was studied by non-equilibrium molecular dynamics simulation. All the filler NPs were in monodispersed state and the interactions between these particles were purely repulsive. The polymer-particle interactions were attractive and their interaction energies were tuned in a broad range. Through the computational study, many important features of the behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 52 publications
(58 reference statements)
1
24
0
Order By: Relevance
“…The deformation frequency is much higher than those that are commonly employed in experimental studies of filled rubbers, but not so high to produce a glassy response of the polymer (see the results section below). It is in line with those employed in other, current simulation studies of polymer networks and nanocomposites [37,75].…”
Section: Dynamical Mechanical Analysissupporting
confidence: 88%
See 1 more Smart Citation
“…The deformation frequency is much higher than those that are commonly employed in experimental studies of filled rubbers, but not so high to produce a glassy response of the polymer (see the results section below). It is in line with those employed in other, current simulation studies of polymer networks and nanocomposites [37,75].…”
Section: Dynamical Mechanical Analysissupporting
confidence: 88%
“…These system sizes are impressive by current standards, but they still fall short of those required to model the hierarchical organization of the nanoparticles into fractal-like structures, such as those which characterize many rubber nanocomposites [ 33 ]. Thus, most simulations of PNCs are still carried out with coarse-grained (CG) models, typically based on bead-and-spring polymer chains and Lennard–Jones-type (LJ) interaction potentials [ 34 , 35 , 36 , 37 , 38 , 39 ] or some appropriate generalization of them [ 40 ]. An even coarser description is the one based on Dissipative Particle Dynamics (DPD) [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…15,16 The dynamics at such small length scales has a remarkable effect on the macroscopic response of the material, including its rheology. The rheological properties of PNCs have been recently assessed in terms of the interactions established between NPs and polymer chains, [21][22][23][24] the nature of the chain attachment to the NP's surface, 25 degree of NPs' dispersion, 26 NP's size 27 and concentration. 28 In particular, in a previous study, we showed that NPs smaller than the R g can reduce the viscosity of the polymer melt and hence act as plasticizers, while particles larger than R g act as thickening agents and significantly increase it.…”
mentioning
confidence: 99%
“…The calculation method of the heat conduction probability is similar to that of the electrical conductive probability from the simulation work of Feng et al, 54 and it is based on the filler overlapping network as mentioned in our previous studies. 48,55 Note that the dots in Fig. 3c represent the simulation data and the continuous line is the corresponding polynomial smooth curve.…”
Section: Spherical Fillers Filled Polymer Nanocompositesmentioning
confidence: 99%